Variation in spawning time promotes genetic variability in population responses to environmental change in a marine fish - Oomen, Rebekah A (Conserv Physiol, 2015)
The level of phenotypic plasticity displayed within a population (i.e. the slope of the reaction norm) reflects the short-term response of a population to environmental change, while variation in reaction norm slopes among populations reflects spatial variation in these responses. Thus far, studies of thermal reaction norm variation have focused on geographically driven adaptation among different latitudes, altitudes or habitats. Yet, thermal variability is a function of both space and time. For organisms that reproduce at different times of year, such variation has the potential to promote adaptive variability in thermal responses for critical early life stages. Using common-garden experiments, we examined the spatial scale of genetic variation in thermal plasticity for early life-history traits among five populations of endangered Atlantic cod (Gadus morhua) that spawn at different times of year. Patterns of plasticity for larval growth and survival suggest that population responses to climate change will differ substantially, with increasing water temperatures posing a considerably greater threat to autumn-spawning cod than to those that spawn in winter or spring. Adaptation to seasonal cooling or warming experienced during the larval stage is suggested as a possible cause. Furthermore, populations that experience relatively cold temperatures during early life might be more sensitive to changes in temperature. Substantial divergence in adaptive traits was evident at a smaller spatial scale than has previously been shown for a marine fish with no apparent physical barriers to gene flow (∼200 km). Our findings highlight the need to consider the impact of intraspecific variation in reproductive timing on thermal adaptation when forecasting the effects of climate change on animal populations.